Consensus in networked multi-robot systems via local state feedback robust control. (10th December 2019) - Zhang, Shijie; Cao, Yi
In the article, the consensus problem is considered for networked multi-robot systems, in which the dynamical equation of all robots is non-holonomic and nonlinear systems. In the multi-robot systems, each robot updates its current states and receives the states from the neighboring robots. Under the assumption that if the network graph is bidirectional, a local information-based state feedback robust controller is designed to make sure the convergence of the individual robots' states to a common value. Finally, the effectiveness of the presented method is illustrated by the simulation results of a group of four mobile robots.